Strengthening international ties: a visit from Universitas Pembangunan Nasional “Veteran” Jakarta / Fazleen Haslinda Mohd Hatta - Mohd Hatta, Fazleen Haslinda (Faculty of Pharmacy, 2024)
On the 3rd of July 2024, the Faculty of Pharmacy at Universiti Teknologi MARA (UiTM) had the honor of hosting a delegation from Universitas Pembangunan Nasional “Veteran” Jakarta, Indonesia. The delegation, led by Dr. Taufiq Fredrik Pasiak, Dean of Medicine, comprised five esteemed members.